Peatland Heterogeneity Impacts on Regional Carbon Flux and Its Radiative Effect Within a Boreal Landscape. Issue 9 (23rd September 2022) - Kou, Dan; Virtanen, Tarmo; Treat, Claire C.; Tuovinen, Juha‐Pekka; Räsänen, Aleksi; Juutinen, Sari; Mikola, Juha; Aurela, Mika; Heiskanen, Lauri; Heikkilä, Maija; Weckström, Jan; Juselius, Teemu; et al.
Abstract: Peatlands, with high spatial variability in ecotypes and microforms, constitute a significant part of the boreal landscape and play an important role in the global carbon (C) cycle. However, the effects of this peatland heterogeneity within the boreal landscape are rarely quantified. Here, we use field‐based measurements, high‐resolution land cover classification, and biogeochemical and atmospheric models to estimate the atmosphere‐ecosystem C fluxes and the corresponding radiative effect (RE) for a boreal landscape (Kaamanen) in northern Finland. Our result shows that the Kaamanen catchment currently functioned as a sink of carbon dioxide (CO2 ) and a source of methane (CH4 ). Peatlands (26% of the area) contributed 22% of the total CO2 uptake and 89% of CH4 emissions; forests (61%) accounted for 78% of CO2 uptake and offset 6% of CH4 emissions; water bodies (13%) offset 7% of CO2 uptake and contributed 11% of CH4 emissions. The heterogeneity of peatlands accounted for 11%, 88%, and 75% of the area‐weighted variability (deviation from the area‐weighted mean among different land cover types (LCTs) within the catchment) in CO2 flux, CH4 flux, and the combined RE of CO2 and CH4 exchanges over the 25‐year time horizon, respectively. Aggregating peatland LCTs or misclassifying them as nonpeatland LCTs can significantly ( p  < 0.05) bias the regional CH4 exchange and RE estimates, while differentiating between drier noninundated and wetter inundated peatlands can effectively reduce the bias. Current land cover products lack such details in peatland heterogeneity, which would be needed to better constrain boreal C budgets and global C‐climate feedbacks. Plain Language Summary: Peatlands form part of the boreal landscapes exhibiting diverse types and microforms that have different characteristics of topography, hydrology, vegetation, and soil. Our understanding is still limited concerning how boreal peatlands, especially their inherent heterogeneities, affect the regional biosphere‐atmosphere exchange of carbon and related climate effects, and what level of detail is needed to characterize them in land cover maps. By combining remote sensing information, field measurements, and biogeochemical modeling, we showed that, among different land cover types, peatlands played a dominant role in the variability of methane (CH4 ) flux (88%) and the combined radiative climate effect due to carbon dioxide and CH4 exchanges (75% over the 25‐year time horizon). Possible aggregation and misclassification of peatland types could induce significant biases in the regional CH4 balances and radiative effect estimates, but the distinction of noninundated drier and inundated wetter peatland types could reduce these biases effectively. Key Points: The atmosphere‐ecosystem carbon exchange of a heterogeneous boreal landscape was determined Peatlands (26% area) contributed 22% total carbon dioxide (CO2 ) uptake and 89% methane (CH4 ) emission; forests offset 6% CH4 emission and water bodies 7% CO2 uptake Differentiating between noninundated drier and inundated wetter peatlands improved radiative effect estimates